MILLENNIAL GENERATION INTERESTING FACTORS IN THE PROCESS OF DEVELOPING CHARACTERS OF PANCASILA DURING ONLINE LEARNING - Angelina, Sabela Ayu (Program Studi PPKn Universitas Pendidikan Ganesha, 2024)
Determining Factors of the Millennial Generation in Running a Country and Good Character Education. Currently hit by the Covid-19 pandemic, changes in government regulations, namely implementing online learning at home, must be carried out by students. The purpose of writing this article is to determine the inhibiting factors for the millennial generation in carrying out online learning during the Covid-19 pandemic, both from normal and abnormal students. Method: The method used is a literature review. Data collection techniques using Google Scholar and Mendeley with a limit of 2019 to 2021. This study focused on the keywords